(3eQShe TQja UGdMis
(3ChdgG (B:s
(3eQShe TQja HCf JYJeO LejY WhGFa GdjghO hGdfUGQi hGdSGeQI HGdOjGQ GdeUQjI hGdHdGO GdESdGejI GdeMQhSI hCYeGdgG Mce YgO CejQ GdeDefjf YeQ Hf GdNWGH dGjMOKhG ai GdHdGO GdESdGejI OjQkG hdG cfjSI s
(3BNQgG (B:s
(3hCf dGjONd fShI Cgd GdPeI GdMeGeGJ eY GdeSdeGJ hjLYd dgf MeGe jNUgf jONdfgG YedkG ai Pdc HeG QLMg YdeGA GdTQY GdTQja s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdJGQjNs